CALCULATING THE DISTRIBUTION OF INHERITANCE ACCORDING TO ISLAMIC LAW USING GAMBAS - Wahyu Setiawan; Riris Ristyawati., SKom, MMSI (Jurnal Sistem Informasi, 2007)
Legacy problem is one thing that could be considered quite important as it can arise only because it is a discord, quarrel or hostility within a family, it is usually because of inappropriate distribution, which raised dissatisfaction of each - each party. In the Islamic Shari'a inheritance problem set in the Al Qur’an, and Hadith, as well as pretty much all the verse – verse Al Qur’an that regulate both the legacy issues and the provisions of the respective decree - and their heirs who get it. In Scientific Writing, the writer tries to simplify the calculation of the distribution of inheritance according to Islamic law by making a computer program to calculate the distribution of Inheritance with language by using Gambas.